2023
DOI: 10.1038/s41408-023-00808-8
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications of bispecific antibody therapy in patients with multiple myeloma

Abstract: Rhinovirus/enterovirus (n = 8), influenza (n = 1), adenovirus (n = 4), COVID-19 (n = 2). 4 BK virus (n = 1), cytomegalovirus (n = 4), herpes simplex virus 2 (n = 1), Epstein Barr virus (n = 1). 5Mycobacterium avium complex (n = 1). 6 Deaths attributed to preceding infection within 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…BCMA-targeted T-cell-redirecting therapies have been linked to a heightened susceptibility to infectious complications due to their mechanism of action 30 33 . Inhibiting BCMA signaling, which is critical for the survival and proliferation of plasma cells, may worsen the pre-existing myeloma-induced immunosupression 31 , 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…BCMA-targeted T-cell-redirecting therapies have been linked to a heightened susceptibility to infectious complications due to their mechanism of action 30 33 . Inhibiting BCMA signaling, which is critical for the survival and proliferation of plasma cells, may worsen the pre-existing myeloma-induced immunosupression 31 , 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Infections have been reported with the use of T-cell-redirecting bispecific antibodies; however, infections were reported less frequently in trials of GPRC5D-targeting T-cell-redirecting bispecific antibodies compared with trials of BCMA-and Fc receptor-like protein 5-targeting bispecific antibodies [58][59][60][61], which may be due to the more limited expression profile of GPRC5D in the immune compartment compared with the expression profiles of these other target antigens [20,21,[25][26][27]. Additionally, the lower expression of GPRC5D on normal plasma cells compared with malignant plasma cells may preserve normal plasma cells during treatment [21,59].…”
Section: Bms-986393mentioning
confidence: 99%
“…The 4 observational studies (141 patients) provided further infection regarding causative pathogen, infection onset, and outcomes ( supplemental Table 4 ). 22 , 23 , 24 , 25 Of the 293 infection events reported in observational studies, 68% were microbiologically-confirmed, including viral (49%), bacterial (45%), and fungal (6%). When reported, gram-negative pathogens were the predominant cause of bacterial infections (64%).…”
Section: Resultsmentioning
confidence: 99%